Solvent Free Synthesis of N-Substituted Pyrrole Derivatives Catalyzed by Silica Sulfuric Acid - Khammas, A. J.; Yolacan, C.; Aydogan, F. (PLEIADES PUBLISHING LTD, 2018)
Sulfuric acid immobilized on silica gel is used as an efficient catalyst in the synthesis of N-substituted pyrrole derivatives by the Clauson-Kaas pyrrole synthesis. The solvent free reaction mixture is stirred by grinding. Within very short reaction time the process leads to the corresponding products without any decomposition recorded.
Keywords: Clauson-Kaas reaction; grinding method; pyrrole; silica sulfuric acid; solid acid catalyst; SOLID ACIDS; EFFICIENT; Chemistry